Investigating whether connecting people can promote subnational economic development: Evidence from China–ASEAN friendship cities - Fangying Pang; Jingjing Tang; Hanwen Xie (International Studies of Economics)
Abstract Whether maintaining a close relationship with China can benefit economic performance in the postpandemic era is a crucial concern for countries around the world. This study employs the difference‐in‐difference (DID) model and propensity score matching to estimate the impact of connecting people proposed by the Belt and Road Initiate (BRI) on the subnational economic development of the Association of Southeast Asian Nations (ASEAN) cities. The quasi‐natural experiment of DID is based on the establishment of China–ASEAN friendship cities. We capture the ASEAN subnational economic development by calibrated satellite nighttime light data. Our findings show that the establishment of a friendship‐city relationship has a positive impact on the subnational economic development of China–ASEAN cities. Further analysis indicates that bilateral trade, China's direct investment in contracted projects, and mutual visits by national leaders may be the underlying channels for boosting the economic development of China–ASEAN friendship cities. This study contributes to the literature on friendship city and provides ex‐ante implications on the BRI from the perspective of connecting people with first‐hand empirical evidence.